Pattern of antimicrobial utilization in indoor ward of surgery department of a tertiary care teaching hospital of Southern Rajasthan, India - Chhipa, Vinod Kumar; Atray, Meena (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug utilization studies are conducted to analyze prescription pattern, facilitate rational prescribing and improve the outcome. Antibiotics are frequently prescribed drugs in surgery department both by oral and parenteral route. Irrational prescribing of antibiotics is responsible for emergence of drug resistance in pathogens which is a global problem now a days. Methods: 225 patients admitted in surgical indoor were included in the study and data collected was evaluated as per WHO quality indicators. Results: Ceftriaxone was maximally utilized antimicrobial (%), average number of antimicrobial prescribed was 2.73±1.08. Average duration of hospitalization was 10.32 days. Costliest antimicrobial prescribed was meropenum and with minimum cost was Clarithromycin. Cost per patient was Rs.72.6. PDD/DDD ratio of Amoxicillin+Clavulanic acid was maximum. 24% of patients were receiving complementary and alternative medicines. Conclusions: The drugs were prescribed from the essential drug list with generic names in appropriate dose and duration. The need of Culture and sensitivity test for selecting antimicrobials was identified in the study. The study can be further expanded by including patients of vulnerable groups and private sector and evaluation of effect of self medication on outcome.